INNOVATIVE ENTREPRENEURS AND THEIR NEGOTIATION BEHAVIOURS IN LAUNCHING NEW PRODUCTS - Nhat Minh, Nguyen; Cong Hiep, Pham; Thi Ouynh, Nguyen; Smith, Phil (Humanities & Social Sciences Reviews, 2020)
Purpose: This study investigates the impact of the negotiation behaviours by Vietnamese innovative-entrepreneurs on negotiation outcomes. The focus emphasises face-to-face negotiation sessions between innovative entrepreneurs and their corporate customers as they promote new services and products that either fulfill unmet market demands or achieve significant improvements in comparison to existing products or services. Methodology: This paper employed a qualitative research method to distill the entrepreneurial negotiation behaviours and their impacts on negotiation performance. A series of semi-structured interviews were conducted individually with 14 Vietnamese innovative-entrepreneurs, from five industries including technology, manufacturing, agriculture, medical, and education. To ensure the entrepreneurs’ fall under the classification of innovative-entrepreneurs. The participating entrepreneurs were selected Entrepreneurship-Incubator, Vietnam-Department-of-Business-Registration-Management, and Business-Startup-Support-Centre. Main Findings: The findings showed that the negotiated-terms, the self-expression of the parties, the negotiation process, and the relationship developed were found to be significant in measuring negotiation performance. Negotiation behaviours, including concern about the personal outcome; concern about othersâ€™ outcomes; building relationships; and, emotional expression, were found as having a positive impact on negotiation performance. In contrast, risk-taking negatively affected negotiation outcomes. Applications: Based on the aforementioned findings, a proposed negotiation-framework of an innovative-entrepreneur in the product launching stage is being developed. Novelty/Originality of this study: This study brings another view on measuring negotiation performance by applying psychological negotiation outcome elements rather than relying on objective elements only. The significance of each psychological negotiation outcome element is also ordered. The unique advantages and challenges of the launching stage of an innovative entrepreneur are also explored to provide in-depth entrepreneurial knowledge.